2022
DOI: 10.3389/fphys.2022.977578
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific association between inflammation and endothelial function relevant gene and vulnerable carotid plaque

Abstract: Objectives: We aimed to explore sex-specific association between genes involved in inflammation and endothelial function and vulnerable carotid plaque, a subclinical precursor of ischemic stroke.Methods: Carotid plaque and plaque phenotype were assessed by carotid ultrasound in high-risk participants for stroke drawn from a multicenter, cross-sectional survey in southwestern China. We examined 18 single nucleotide polymorphisms (SNPs) in 10 genes related to inflammation and endothelial function. Sex difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Genetic factors play an important role in the development of carotid atherosclerosis (Gardener et al., 2011 ; Grbić et al., 2022 ). Multiple risk factors may influence the relationship between the gene polymorphisms and carotid atherosclerosis (Li et al., 2022 ; Maitusong et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic factors play an important role in the development of carotid atherosclerosis (Gardener et al., 2011 ; Grbić et al., 2022 ). Multiple risk factors may influence the relationship between the gene polymorphisms and carotid atherosclerosis (Li et al., 2022 ; Maitusong et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms associated with inflammation and endothelial function may directly or indirectly interact with vascular risk factors to influence the onset and progression of atherosclerosis (Galkina & Ley, 2007 ; Gardener et al., 2011 ; Zhang et al., 2007 ). Previous studies have shown that multiple risk factors have an impact on the relationship between genes and carotid atherosclerosis, so it is necessary to analyze the correlation between genes and carotid atherosclerosis by combining multiple factors (Li et al., 2022 ; Maitusong et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have reported a higher prevalence and incidence of carotid plaques in men than in women [ 30 ]. Possible reasons include the sex-specific nature of genes involved in inflammation and endothelial function [ 43 ] and sex differences in carotid bifurcation anatomy [ 44 ]. The subgroup analysis in our study also suggested that females were more likely to benefit from such lipid-regulating measures, thereby reducing the risk of carotid plaque occurrence.…”
Section: Discussionmentioning
confidence: 99%